Nature Medicine - Monteiro, Joao.; SpringerLink (Online service) (New York : Nature Publishing Group US : Imprint: Nature Research.)
Original research articles published in Nature Medicine range from basic findings that have clear implications for disease pathogenesis and therapy to the earliest phases of human investigation. Aiming to keep Ph.D. and M.D. readers informed of a wide range of biomedical research findings, the journal publishes the latest advances in cancer biology, vascular biology, neuroscience, inflammatory disease, infectious disease and metabolic disorders, among other fields. Reviews, Perspectives and other commissioned content clarify and give context to these biomedical research advances, and the News section reports on the latest developments in drug research and development.
Keywords: Medicine; Cancer research; Molecular biology; Neurosciences; Infectious diseases; Metabolic diseases; Biomedicine, general; Cancer Research; Metabolic Diseases; Infectious Diseases; Molecular Medicine; Neurosciences